DEKONSTRUKSI ISLAM DAN LIBERALISME DALAM TAFSIR MAUDHUI: Menelusuri Makna Kebebasan Menurut al-Qur’an - Sheila Khoerunisa; Arief Kurniawan; Lala Nur Indrawati; Muhammad Kahfi Syabani (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2025)
Islam is a religion that comes from revelation while liberalism is an ideology that comes from the modern tradition of thought which has a different background and value base. Conflicts between the two often arise in various spheres of life, ranging from politics to culture, especially in debates about the limits of individual freedom, the role of religious law, and the role of the state in regulating its society. At the same time, developments in contemporary discourse show that the two are not entirely opposed to each other. In these situations, there is an opportunity for interaction that connects Islamic teachings and liberal principles in an analytical and constructive manner. With this, it is very necessary to take a dialogical and contextual approach in understanding the relationship between these two systems of thought, in order to create a more balanced and inclusive understanding in facing the challenges of this era.